2012
DOI: 10.2741/e584
|View full text |Cite
|
Sign up to set email alerts
|

A high-throughput screen to identify inhibitors of SOD1 transcription

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal degenerative motor neuron disease. Approximately 20% of familial ALS cases are caused by mutations in the Cu/Zn superoxide dismutase (SOD1) gene. Rodents expressing mutant SOD1 transgenes develop progressive, fatal motor neuron disease and disease onset and progression is dependent on the level of SOD1. We investigated the possibility that a reduction in SOD1 protein may be of therapeutic benefit in ALS and screened 30,000 compounds for inhibition of SOD1 transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…And, Benmohamed et al (39) developed a cellular model in which the readout is the blocking of mutant SOD1-induced aggregation. Furthermore, Wright et al (40) used the inhibition of SOD1 as their readout. What these methods lack is simplicity.…”
Section: Resultsmentioning
confidence: 99%
“…And, Benmohamed et al (39) developed a cellular model in which the readout is the blocking of mutant SOD1-induced aggregation. Furthermore, Wright et al (40) used the inhibition of SOD1 as their readout. What these methods lack is simplicity.…”
Section: Resultsmentioning
confidence: 99%
“…In one screening, most of the drugs that were able to reduce the promoter activity also reduced cellular viability while no drug resulted in specific reduction of SOD1 protein 150 . In the second study only 3 compounds showed significant effect in reducing the promoter without affecting cell survival 82 . Compound number 7687685 was the only one able to reduce the amount of SOD1 mRNA and protein also when tested in a human cell line (HeLa cells).…”
Section: Reviewmentioning
confidence: 92%
“…In particular, many investigators using different methods proved that the reduction of the human SOD1 protein was beneficial in rescuing the ALS phenotype 75–77 , in delaying the onset and/or increasing the life span of animal models of ALS 6,78,79 . Different methods have been applied to achieve direct or indirect reduction of the SOD1 protein through administration of small molecules 80–82 or antibodies 83,84 , or the application of RNA technologies, including microRNAs 85,86 , RNAi 77,79,87–89 and antisense Oligonucleotides (ASO) 90 . Of great interest is the first human clinical trial conducted by Richard Smith and Tim Miller and his team in collaboration with Ionis Pharmaceuticals, involving the intrathecal delivery of an ASO against SOD1.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreasing the expression of SOD1 has also been explored as a therapeutic avenue to reduce SOD1 expression in ALS. Compounds that inhibit SOD1 transcription in model cell lines have been identified, and may serve as the basis for developing clinically viable strategies for ALS aimed at decreasing SOD1 expression (66).…”
Section: Sod1 Function In Alsmentioning
confidence: 99%